Employee performance appraisal using individual performance management - Erialdy, Erialdy (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The performance appraisal system or process has a very important function for the human resource management division to measure the human resource management governance system in order to achieve the company goals, vision and mission. The Regional Drinking Water Company Tirta Kerta Raharja is a company that has a good performance in terms of finance, service, and human resources with the title of first national PDAM with the best performance in 2019 and 2020, using individual performance management (MUKI) as a guide in conducting employee performance appraisal. This study aimed to provide the overview of individual performance management that is expected to provide benefits for those interested in assessing individual employee performance. Collecting data using observation techniques, interviews and documentation studies and looking for reference studies. In conclusion, individual performance management is considered important in a company for achieving the goals. Company performance is inseparable from individual’s role in carrying out their job duties as the driving force for running of the company, a leader can judge his employees when he knows that is done and produced by these employees, it is obtained from the individual employee success in carrying out a job.